SOCIAL MEDIA AS A CATALYST FOR THE DEVELOPMENT OF TOURISM BUSINESS: A STUDY OF TOURISM INDUSTRY OF PAKISTAN - Rafiq, Khushboo; Lakho, Muhammad Kamil; Jaffiry, Kumail Abbas (Journal of Business & Tourism, 2023)
The accelerating trend of social media usage has allowed users to gain knowledge about the tourism experiences of other people through reactive and proactive interactions. The primary aim of this study is to identify whether social media is playing a constructive role in increasing the development and productivity of the tourism business. The research also evaluates the effects and advantages of earned media marketing tools over social media advertisements shared by tourism companies in the process of deciding about tourism packages. This research consists of a quantitative approach. A random sampling method has been adopted by researchers to disseminate closed-ended questionnaires and a total of 206 responses were collected. After applying the reliability test through SPSS, data were examined through ANOVA and Tukey’s HSD testing. Results determined that people are more eager towards seeing and gaining public opinion than the promotions and advertisements shared on social media by tourism companies. They especially consider the experiences and viewpoints of their close relations like relatives, friends, and colleagues as well as Vloggers and social media influencers while deciding to visit a tourist spot. Because of the findings, it can be recommended that tourism companies should focus more on earned media marketing tools than traditional advertising techniques while designing their marketing strategies.